Transplacental transmission of Toxoplasma gondii in reinfected pregnant female canines - Bresciani, Katia Denise Saraiva [UNESP]; Costa, A. J. [UNESP]; Toniollo, Gilson Hélio [UNESP]; Luvizzoto, M. C. R. [UNESP]; Kanamura, C. T.; Moraes, Flávio Ruas de [UNESP]; Perri, S. H. V. [UNESP]; Gennari, S. M. (Springer, 2009)
Twelve pregnant female canines, naturally infected with Toxoplasma gondii, were reinfected with T. gondii: three (GI) received tachyzoites subcutaneously (1.0 x 107), three (GII) were orally inoculated with oocysts (1.5 x 104), and six (GIII) were kept as a nonreinfected control group. All the reinfected female canines (GI and GII) miscarried or presented fetal death, while only one GIII female presented a stillborn in a litter of four pups (P < 0.01). Fever, lymphoadenopathy, miscarriage, and fetal death were the main clinical alterations observed. The highest serological titers detected through the indirect fluorescence antibody test (IFAT) were 1,024 (GI) and 4,096 (GII). In group III, the titers ranged between 64 and 256. By bioassays in mice, T. gondii was isolated in 17 organs of the reinfected adult canines, in 11 of the control group, and in 20 of the neonates. Positive immunostaining of cysts and/or tachyzoites were observed in 26 canine tissues (14 from GI and GII and ten from GIII). The agent was detected by immunohistochemistry in the encephalon of a neonate and in the spinal cord of a stillborn, thus, confirming that T. gondii infected canine fetuses, provoking miscarriages, even in bitches that presented primoinfection.